Mismatch repair protein and MLH1 methylation status as predictors of response to adjuvant therapy in endometrial cancer - Mikko Loukovaara; Annukka Pasanen; Ralf Bützow (Cancer Medicine, 2021)
Abstract Background Mismatch repair (MMR) system has been implicated in the response of mammalian cells to ionizing radiation and DNA damaging agents. We investigated the value of the MMR system in predicting response to adjuvant therapy in endometrial cancer. Methods This was a single institution retrospective study. MMR protein status of endometrial carcinomas was assessed by immunohistochemistry. MMR deficient (MMR‐D) tumors were identified as MLH1 methylated or nonmethylated by methylation‐specific multiplex ligation‐dependent probe amplification. Tumors with abnormal p53 staining or polymerase ϵ exonuclease domain mutation were excluded from the MMR proficient subgroup, which was termed as “no specific molecular profile” (NSMP). Disease‐specific survival analyses were adjusted for age, stage, histology and grade, depth of myometrial invasion, and lymphovascular space invasion. Results A total of 505 patients were included in the study. Median follow‐up time was 81 months (range 1–136). Whole pelvic radiotherapy (adjusted hazard ratio [HR] 0.092 vs. no adjuvant therapy) and chemotherapy combined with radiotherapy (adjusted HR 0.18) were associated with improved disease‐specific survival in the NSMP subgroup (n = 218). In contrast, adjuvant therapies showed no effect on disease‐specific survival in the full MMR‐D cohort (n = 287) or in MLH1 methylated tumors (n = 154). Whole pelvic radiotherapy (adjusted HR 25 vs. no adjuvant therapy/vaginal brachytherapy) and chemotherapy combined with whole pelvic radiotherapy (adjusted HR 32) were associated with poor disease‐specific survival in MMR‐D nonmethylated tumors (n = 70). Conclusion MMR protein and MLH1 methylation status predict the response to adjuvant therapy in endometrial cancer. The MMR system could be utilized for selection of patients who most likely benefit from adjuvant therapy.